Czynniki ryzyka zawierające się w środowisku rodzinnym, w którym wystąpiła ingerencja sądu rodzinnego we władzę rodzicielską poprzez odebranie dziecka rodzicom – wyniki badań - Danielewicz, Paulina (Studia Edukacyjne, 2026)
I conducted research aimed at describing and interpreting the life situations of families from whom children were taken, and specifically at identifying risk factors present in the family environment as well as the relationships between family members. Understanding the life situations of parents whose children were taken helps to better comprehend the mechanism of court intervention in parental authority, and to design measures to limit the use of child removal procedures by the authorities. In the following article, I will present the results of research conducted in one of the district courts in a county town in Poland.